Hepatitis B Virus Infection in Tanzania: Current Status and Challenges - Semvua B. Kilonzo; Daniel W. Gunda; Bonaventura C. T. Mpondo; Fatma A. Bakshi; Hyasinta Jaka (Journal of Tropical Medicine)
Hepatitis B is one of the most common infectious diseases in the world with high prevalence in most of sub-Saharan Africa countries. The complexity in its diagnosis and treatment poses a significant management challenge in the resource-limited settings including Tanzania, where most of the tests and drugs are either unavailable or unaffordable. This mini review aims at demonstrating the current status of the disease in the country and discussing the concomitant challenges in diagnosis, treatment, and prevention.